2005
DOI: 10.3758/bf03193625
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the structural determinants of object confusion in memory: An assessment of psychophysical approaches to estimating visual similarity

Abstract: Computer-generated shapes varying on visual dimensions such as curvature, tapering, and thickness have been used to investigate identification deficits in the category-specific visual agnosia (CSVA) Patient E.L.M.. However, whether the implemented variations on each of these dimensions were perceived by novice observers as "similar amounts of change" is unknown. To estimate distance in psychophysical shape space, sets of shapes were developed using two different scaling methods-an objective method based on vis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…The goal of Experiment 1 was to look individually at action space and 3-D object space to demonstrate that the similarity relationship demonstrated by Desmarais and Dixon (2005) also exists for the visual identification of 3-D objects and actions. Participants learned to identify novel objects and novel actions with pronounceable nonwords.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The goal of Experiment 1 was to look individually at action space and 3-D object space to demonstrate that the similarity relationship demonstrated by Desmarais and Dixon (2005) also exists for the visual identification of 3-D objects and actions. Participants learned to identify novel objects and novel actions with pronounceable nonwords.…”
Section: Methodsmentioning
confidence: 99%
“…), similarity was either intuitively determined or determined by participants' subjective similarity ratings (Dixon et al, 1997;Dixon et al, 1999;Dixon et al, 2002;Schweizer, Dixon, Desmarais, & Smith, 2002). Dixon et al (1997) and Desmarais and Dixon (2005) have shown that participants' subjective ratings of visual similarity do not adequately reflect similarity in memory space. In the current experiments, the consistent main effect of similarity attests to the importance of visual similarity in visual object identification.…”
Section: Implications For Visual Object Identificationmentioning
confidence: 99%
See 3 more Smart Citations